(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2022)
Sadhguru Jaggi Vasudev, a yogi and mystic, is the man behind the Isha Foundation and itsnetwork of Yoga institutes. The Sadhguru has been a featured speaker at several prestigious InternationalLeadership Forums. He has attended the US Millennium Peace Summit, the World Peace Congress, andthe World Economic Forum in Devos on several occasions. Sadhguru’s life and teachings are a strikingexample of how the ancient practice of yoga can be modernized into a cutting-edge science that iscritically relevant to today’s youth in our technologically sophisticated society. In this paper review themystic world of Sadhguru Jaggi Vasudev.